Geochemical study of the Louis Lake Batholith and its potential as a fluid source for gold deposits in the Atlantic City District, WY - Vaughn, Elizabeth, author; Ridley, John R. (John Robert), advisor; Hannah, Judith L., committee member; Ladanyi, Branka, committee member (Colorado State University. Libraries, 2010)
To view the abstract, please see the full text of the document.
Keywords: mineralization; fluid inclusions; Louis Lake Batholith; gold; Batholiths -- Wyoming -- Wind River Range; Fluid inclusions -- Wyoming -- Wind River Range; Gold ores -- Geology -- Wyoming -- Wind River Range